2016
DOI: 10.18097/pbmc20166202154
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xenobiotics on microrna expression in rat liver

Abstract: Using bioinformatics analysis we selected microRNAs which could bind 3'-UTR-region of cytochrome P450 (CYP) genes. Three microRNA miR-21, -221, -222, their potential targets might be mRNA for CYP1A1, and two microRNA miR-143, miR-152 for CYP2B1 accordingly were selected for experimental verification. Expression level of these microRNAs in rat liver upon benzo(a)pyrene (BP), phenobarbital (PB), and DDT induction was determined using RT-qPCR method. In rats treated by both BP, and DDT the hepatic content of miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It was previously shown that miRNA levels are induced or repressed following animal exposures to chemical insecticides. For example, miR-21 , miR-221 , and miR-222 expression levels were estimated to be 2–3 times lower in DDT-treated rat liver compared to untreated controls (Gulyaeva et al, 2016). Recently, analogous levels of differential miRNA expression patterns were associated with insecticide resistance or were shown to be induced following exposure to insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that miRNA levels are induced or repressed following animal exposures to chemical insecticides. For example, miR-21 , miR-221 , and miR-222 expression levels were estimated to be 2–3 times lower in DDT-treated rat liver compared to untreated controls (Gulyaeva et al, 2016). Recently, analogous levels of differential miRNA expression patterns were associated with insecticide resistance or were shown to be induced following exposure to insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…Another change that DDT can cause at the epigenetic level is the expression of miRNAs. The characterization of miRNA can vary depending on the type of tissue or cells that are analyzed (121). A study performed in rodents showed a significant positive modulation of miRNA in hepatic cells.…”
Section: Dichlorodiphenyltrichloroethane (Ddt)mentioning
confidence: 99%
“…Therefore, it is viable to state that DTT may modulate miRNA for those genes involved in detoxification, such as genes that encode for CYP enzymes. It has been postulated that a plausible mechanism is DNA methylation (121). The available scientific tools, of the modern world, have allowed us to get acceptable evidence of the long-term exposure to DTT and its effects on the biological system.…”
Section: Dichlorodiphenyltrichloroethane (Ddt)mentioning
confidence: 99%
“…Distinct mechanisms of regulation of miRNA expression can occur in cell: transcriptional (changes in gene expression and promoter hypermethylation) and post-transcriptional (changes in miRNA processing), as well as effects of endogenous (hormones, cytokines) and exogenous (xenobiotics) compounds on the miRNA expression (reviewed in [105,106]).…”
Section: Regulation Of Mirna Expression and Therapeutic Perspectivesmentioning
confidence: 99%